THE POSTULATION OFLEADERSHIP SKILLS AMONG HEADS OF BUSINESS EDUCATION IN OGUN STATEOWNEDUNIVERSITIES - K. O. Odunaike; A. O. Okusanya; M. B. Amoda (European Scientific Journal, ESJ, 2014)
The paper looks at how leadership skills can be improved among the heads of Business Education in the Ogun-state owned Universities.It was noted that Business Education in the study area is a sub-component unit ofdepartments therebydiscouraging intimate and direct relationship between the leader andsubordinates in the Institutions. The paper identifies fivepossible leadership styles of Business Education heads and discusses how leaders can improveon their skills in the universities. It is recommended that the leader should make the subordinates feel important and gain their willingness to work.The paper concludes that a quality leader makes both the task and the experience better. Not only does everyone start somewhere, but no one ever stops learning and expanding in experience and knowledge. The paper also concludes that a good leader must be proactive.